The Effect of Herbal Treatment against Tick - Sahu, P.; Gaherwal, S.; Kanhere, R.R. (International Journal of Scientific Research in Biological Sciences, 2021)
The present study was done with the use of effective herbal plant extracts against ticks to estimate the acaricidal activity. Two herbal plant i.e. Azadirachta indica (Neem) and Allium sativum (Garlic) were used as an extract against different species of ticks (Hyalomma anatolicum, Boophilus microplus and Rhiphicephalus) which were highly reactive to ticks mortality. In the present study, when Allium sativum plant extracts were used it showed 100 % tick mortality within 43 minutes and Azadirachta indica showed 100 % tick mortality within 30 minutes The combination of both the plant extracts showed 100 % tick mortality within 20 minutes.